The transformation of capacity in international development : Afghanistan and Pakistan (1977-2017) - Mayville, Avideh Kobra (Anthem Press, 2020)
"The Transformation of Capacity in International Development" exposes the transformation of capacity within the development discourse through a discursive analysis of USAID projects in Afghanistan and Pakistan between 1977 and 2017. Capacity development has emerged as a pervasive component and objective of aid, in spite of being ill-defined by donors. USAID is a significant actor with an unrivaled role in the production of projects, providing a unique institutional vantage point from which to realize relationships and networks of aid production. As development agendas increasingly call for human rights approaches to development and the foreign policies of donor states sound alarms over global security threats, capacity development has emerged as the solution to the complex problem of development. Through this examination of USAID's attempts to build capacity in Afghanistan and Pakistan, the book exposes how Western notions of progress, constructed by institutions, government officials, scholars and private sector actors, are obscured by the transformation of capacity. As agendas are translated into projects, they perpetuate historical relationships of global inequality that have corrupted and compete with Indigenous models of governance. "The Transformation of Capacity in International Development" has implications for those considering the future of human rights-based approaches to development, the international management of global security threats and the sustainability of donor investments